Manipulating the taste-related composition of strawberry fruits (Fragaria x ananassa) from different cultivars using deficit irrigation - Bordonaba, J. Giné; Terry, Leon A. (Elsevier, 2010)
Demand and, consequently, production of strawberry fruits has increased over the past few years and, as a result, the water abstractions for cultivation of this fruit have risen considerably. To limit the amounts of water used for several horticultural crops, water deficit irrigation (DI) has been seen as a potential alternative for new cultivation systems. DI in strawberry fruits is generally associated with reduction in berry size and yield; however, a recent study demonstrated that DI on strawberry can increase the concentration of some taste- and health-related compounds in fruits from cv. Elsanta. Hence, the aim of the present study was to further corroborate such findings and to assess the response (and variability) among different strawberry cultivars (namely Christine, Elsanta, Florence, Sonata and Symphony) to imposed water-DI conditions. Water-DI affected both fruit physiology and biochemistry. Nevertheless, the response to drought stress was different for each of the cultivars tested. Plants from cvs. Elsanta, Sonata and Symphony showed a greater reduction in berry size, accompanied by a significant increase in dry matter content for fruit harvested from DI-treated plants. Concomitant to this, and where dry matter was increased, the concentrations of sugars and some acids were generally higher in DI-derived fruit. In contrast, cvs. Florence and Christine did not show significant variations in berry weight or any of the target analytes measured when grown under the conditions imposed in this study. The results presented herein suggest that reducing water irrigation between flower initiation and fruit harvest may be a viable technique for increasing the concentrations of taste-related compounds in cvs. Elsanta, Sonata and Symphony and it may not have a negative impact on overall fruit size of cvs. Christine and Florence.
Keywords: Berry size; dry matter; organic acids; sugars; sweetness